Suitability of 3-trash-fish species in the manufacture of surimi in Bangladesh - Nowsad, A A K M; Uddin, M H; Niwa, E (The Indian Journal of Animal Sciences, 2012)
Trash fish or low priced fish contributes considerably to the fish landings in Bangladesh. These fishes could be utilizedmore profitably by value addition. The present work is an attempt as such value addition viz. surimi production. Threespecies of commonly occurring trash fish were chosen for the present study. The gel forming ability of sea catfish Tachysurusthalassinus, silver belly Leiognathus bindus and jew fish Otolithoides microdon was studi to investigate the suitabilityu ofthese species in the commercial manufacture of surimi.Two-step heating process improved the gel quality in all fishes. T. thalassinus and L. bindus showed peak setting abilityat-40Â°C, while O. microdon showed highest setting at 35Â°C. Both set gel and the cooked product produced from L. bindus werefound inferior when compared with T. thalassinus and O. microdon. Biological characteristics and ready availability of cheapraw material suggest that T. thalassinus and O. microdon could be used in surimi production.